Avaliações de equações aplicadas a análise de fadiga térmica de baixo ciclo para o aço AISI H13 - Silva Neto, Francisco Rodrigues da (Universidade Federal Rural do Semi-Árido, 2019)
The present work aims to evaluate the equations applied to the low cycle thermal fatigue analysis for AISI H13 steel. Thermal fatigue cracks are the result of repeated heating and cooling cycles, producing alternative expansion and contraction. When the metal cools, it contracts and if prevented from moving freely will cause residual tensile stresses. If this alternative expansion and contraction continues, fatigue cracks will form and propagate each time the metal is cooled. For the development of the work, the Coffin and Manson Equation for fatigue life time was used and as basis for model evaluation was taken the studies on thermal fatigue of the authors Maim and Norstron, where they developed a model of thermal fatigue related to fatigue. Tool steels in hot work applications, and the studies by LU Y et al (2019); where a new model of thermal fatigue induced in H13 steel die for pressure die casting was performed. The results were entered into commercial software such as Matlab® and Microsoft Excel® and subsequently plotted graphs for analysis and due comparisons of results. The first study did not present satisfactory results according to the engineering, because the experimental error varied between 1 and 26%, while the second model, with the aid of computer software, obtained results more consistent with reality, since the calculated error of approximately 3%.
Monografia
Keywords: Fadiga; Temperatura; Trincas; Contração; Expansão; ENGENHARIAS::ENGENHARIA MECANICA